IMPLEMENTASI KURIKULUM MERDEKA DI SDN 1 KLEPU - Farhan Rendi Triatma; Melik Budiarti; Naniek Kusumawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to describe the implementation of the Independent Learning Curriculum at SDN 1 Klepu. Through the description presented, it is hoped that you will be able to find out how the Medeka curriculum is implemented at SDN 1 Klepu and be able to identify deficiencies that need to be addressed. This research approach is qualitative research, using qualitative (descriptive) research or naturalistic descriptions of field findings, or those based on field conditions. In this research, the collection methods included observation, interviews and documentation. The validity of research data was carried out using the data triangulation method. The results of research on the implementation of the independent curriculum at SDN 1 Klepu include aspects of the use of teaching tools and aspects of the project to strengthen students' Pancasila profile.